Going Concern Audit Opinion for Indonesian Banking Companies - Junaedy; Rosita Ibrahim (Value Relevance: Jurnal Akuntansi, 2024)
This research aims to determine the influence of company size, audit quality, profitability, and leverage ongoing concern audit opinion. This research analyzes banking companies listed on the Indonesia Stock Exchange for 2020-2022. The data used is secondary data from the company's annual financial reports. The population in this research is all banking companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling, with the final observation sample obtained from 117 company years. The analysis technique used is Logistic Regression Analysis using the SPSS 22.0 program. The research results show that audit quality, profitability and leverage influence going concern audit opinion. The ability to explain going concern audits by the variables audit quality, profitability, and leverage is as big as 31.78%.